2017
DOI: 10.1590/s0004-2803.201700000-43
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of Anti-TNF Therapy in Crohn’s Disease Management: A Brazilian Single-Center Direct Retrospective Comparison Between Infliximab and Adalimumab

Abstract: BACKGROUND: Infliximab and adalimumab are considered effective drugs in the management of Crohn’s disease. However, due to significant immunossupression, they can cause important adverse events, mostly infections. OBJECTIVE: The aim of this study was to quantify and describe adverse events derived from adalimumab and infliximab use in Crohn’s disease patients, and to compare the safety profile between these two agents. METHODS: This was an observational, single-center, longitudinal, retrospective study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…The short‐term efficacy, including achievement of steroid‐free remission, and the continuation of the first anti‐TNF agent were similar between the patients treated with IFX first and those treated with ADA first, and these results were consistent with those reported in previous studies . The similarity of our patient characteristics and short‐term outcomes with those in previous studies suggests a high level of confidence in the quality of our long‐term outcome analysis, which is the highlight of the current study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The short‐term efficacy, including achievement of steroid‐free remission, and the continuation of the first anti‐TNF agent were similar between the patients treated with IFX first and those treated with ADA first, and these results were consistent with those reported in previous studies . The similarity of our patient characteristics and short‐term outcomes with those in previous studies suggests a high level of confidence in the quality of our long‐term outcome analysis, which is the highlight of the current study.…”
Section: Discussionsupporting
confidence: 89%
“…No head‐to‐head comparisons have been performed regarding which agent, IFX or ADA, should be administered first for biologic‐naïve CD patients. Therefore, several retrospective and a few prospective studies have compared the rates of clinical or steroid‐free remission, surgery, loss of response (LOR), and adverse events between patients who received IFX first and those who received ADA first . However, most of these previous reports evaluated relatively short‐term outcomes only and discontinued observation of patient clinical courses at the first episode of LOR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term therapeutic use of anti-TNF carries with it safety issues which include potential for development of skin lesions, immune reactions, peri-operative complications, infections, cancers and decreased fertility/adverse effects on pregnancy [79,110]. …”
Section: Adverse Effects Of Anti-tnf Therapy In CDmentioning
confidence: 99%
“…Recent single and multicenter cohort studies have reported a significant burden of adverse events with anti-TNF therapies including an increased risk of lymphoma independent of the use of concomitant thiopurine therapy ( 8 , 9 ). The anti-integrin vedolizumab and the IL-12/23 antibody ustekinumab are both licensed as second-line biologic therapy for refractory CD.…”
Section: Introductionmentioning
confidence: 99%